2009
DOI: 10.1089/jwh.2008.1226
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Domestic Violence among Mongolian Women

Abstract: Domestic or intimate partner violence (IPV) is widespread in Mongolia and is usually committed in family circles, often away from public view. This study suggests that increasing employment for men may help reduce poverty and alcohol abuse and, thus, IPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…The prevalence of violence among sex workers was higher than those among the general population of women in Mongolia (Oyunbileg, Sumberzul, Udval, Wang, & Janes, 2009). Such high prevalence of violence is consistent with studies of FSWs in other parts of the world.…”
Section: Discussionmentioning
confidence: 90%
“…The prevalence of violence among sex workers was higher than those among the general population of women in Mongolia (Oyunbileg, Sumberzul, Udval, Wang, & Janes, 2009). Such high prevalence of violence is consistent with studies of FSWs in other parts of the world.…”
Section: Discussionmentioning
confidence: 90%
“…Prior to participating in the intervention, 50% to75% of women in the current study reported experiencing physical violence from a paying partner and 26% to 36% experienced sexual violence from a paying partner in the past 3 months. These rates are more than double the violence rates for women in Mongolia, of whom about 18% experienced physical violence and 10% experienced sexual violence in the past 6 months (Oyunbileg et al, 2009). Our findings also indicate that women who exchange sex are also more likely to experience physical (38%-52%) and sexual violence (12%-16%) from an intimate partner as compared to other women in Mongolia.…”
Section: Discussionmentioning
confidence: 99%
“…However, these symptoms are invisible in most cases [11]. Various factors such as poverty, addiction, psychologic disorder, female,alcolism, drug and alcohol use have found as arousing factors in incidence of violence [3,7,[12][13][14]. Also, verbal, physical, and financial violence are related with economic situation of people so that they are prevalent in labors and poor communities [14].…”
Section: Introductionmentioning
confidence: 99%